Pembentukan Karakter Disiplin dan Tawadhu’ Santri Melalui Pembiasaan Membaca Asmaul Husna di Pondok Pesantren Hidayatul Mubtadiin Lampung Selatan - Alfi Rizki Khasanah; Etika Pujianti; Finy Muslihatuzzahro (Journal on Education, 2024)
The main objectives of this research are: 1) To find out how the discipline and tawadhu' character of santri are formed through the habit of reading Asmaul Husna. 2) To find out what factors influence the formation of santri discipline and tawadhu' through the habit of reading Asmaul Husna. This research method uses a qualitative descriptive method. Data sources use primary and secondary data sources. Data collection techniques include observation, interviews and documentation. Data analysis techniques use data reduction, data presentation and drawing conclusions. The results of research carried out by researchers regarding the formation of the character of discipline and tawadhu of santri through the habit of reading Asmaul Husna together at the Hidayatul Mubtadiin Islamic Boarding School, Sidoharjo, Jati Agung, South Lampung, is to equip the female students not only with their religion, but at the Islamic Boarding School there is also non-traditional education. formal which makes the Hidayatul Mubtadiin Islamic Boarding School popular. Supporting factors in forming the character of discipline and tawadhu among students through the habit of reading Asmaul Husna together at the Hidayatul Mubtadiin Islamic Boarding School in Sidoharjo, Jati Agung, South Lampung are encouragement from themselves, the management, ustadz and ustadzah, and infrastructure. The inhibiting factors are the lack of self-awareness of female students, the boarding school environment, lack of consistent attitude and discipline of female students. and infrastructure.